A biomimetic potentiometric sensor based on molecularly imprinted polymer for the determination of memantine in tablets. Issue 6 (18th April 2012) - Arvand, Majid; Samie, Hedyeh Asadi
<x xml:space="preserve">Abstract</x> Memantine hydrochloride is one of the first novel class medications for treatment of Alzheimer's disease. In this work, a biomimetic potentiometric sensor, based on a non‐covalent imprinted polymer, was fabricated for the recognition and determination of memantine in pure drug and tablet pharmaceutical form. The molecularly imprinted polymer was synthesized by precipitation polymerization, using memantine hydrochloride as a template molecule, methacrylic acid as a functional monomer, and ethylene glycol dimethacrylate as a cross‐linking agent. The sensor was developed by dispersing the memantine imprinted polymer particles in dibutyl sebacate plasticizer and embedding in poly(vinyl chloride) matrix. The wide linear range (10−5−10−1 M), with a near Nernstian response of 57.4 mV/decade, a limit of detection 6.0 × 10−6 M, fast response time ( 15 s) and a satisfactory long‐term stability (4 months) are characterizations of the proposed sensor. The sensor showed a high selectivity and a sensitive response to the template in aqueous system. The standard electrode potentials were determined at different temperatures and used to calculate the isothermal coefficient of the electrode. It was used as indicator electrode in potentiometric determination of memantine in pharmaceutical formulations. Copyright © 2012 John Wiley & Sons, Ltd.